2020
DOI: 10.3390/ijerph17072588
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation as the Secret Ingredient in the Recipe to Foster Internal Technological Eco-Innovation in the Agri-Food Industry

Abstract: Although eco-innovation in the agri-food sector is receiving increasing amounts of attention, there is a lack of information about the specific conditions that encourage firms to develop eco-innovation strategies internally. Our empirical method relies on the data of Spanish firms operating in the agri-food sector, and uses the Qualitative Comparative Analysis (QCA). Specifically, we identify the recipes of antecedent conditions that effectively foster the internal development of technological eco-innovation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 99 publications
(167 reference statements)
0
13
0
Order By: Relevance
“…These consumer demands are encouraging enterprises in the food sector to innovate. The literature points to three main determinants of eco-innovation (Rabadán et al, 2020): (1) the market pull that can occur when consumers are willing to pay more for green products (Li & Kallas, 2021); (2) regulatory actions, whereby policies (i.e. tax and regulatory incentives) encourage market change (Triguero et al, 2018); and (3) technological developments, which can occur either internally within a company or externally via collaboration (Rabadán et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…These consumer demands are encouraging enterprises in the food sector to innovate. The literature points to three main determinants of eco-innovation (Rabadán et al, 2020): (1) the market pull that can occur when consumers are willing to pay more for green products (Li & Kallas, 2021); (2) regulatory actions, whereby policies (i.e. tax and regulatory incentives) encourage market change (Triguero et al, 2018); and (3) technological developments, which can occur either internally within a company or externally via collaboration (Rabadán et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Sustainable product innovation, together with its determinants and consequences, has been widely studied in the literature [ 6 , 15 , 46 ]; however, there are still some firm variables that have not been brought to the forefront and that we think are important, e.g., firm growth. Although some efforts have been made to study financial resources as an antecedent of sustainable product innovation [ 22 ], firm growth as a driver of sustainable product innovation has not received attention in the literature. Thus, this study introduced firm growth, in terms of employees and turnover increase, as a driver for sustainable product innovation, contributing to the introduction of sustainable products in the firm.…”
Section: Discussionmentioning
confidence: 99%
“…However, as noted by Tariq et al [ 6 ], extensive research supports the notion that sustainable product innovation generally drives financial performance, but little efforts have been made to study financial performance as an antecedent of sustainable product innovation. For example, we found that Rabadán et al [ 22 ] studied the influence of financial resources and profit levels in the adoption of eco-innovation in the agri-food industry. Similarly, Azari et al [ 23 ] demonstrated positive and significant associations between the firm’s growth ambition and the pursuance of product and business model innovations in manufacturing and service sectors.…”
Section: Introductionmentioning
confidence: 99%
“…However, the scientific debate on sustainable innovations, more commonly defined as eco-innovations, has only developed recently [22,23] and studies on the agri-food sector are still limited. Overall, the literature has focused on the determinants of eco-innovations [24,25], identifying three main drivers: the market pull, the regulatory push/pull, and the technology push. Specifically, the increasing demand of citizen-consumers for sustainable products and their greater willingness to pay, represent a push for companies toward eco-innovations [3,[26][27][28].…”
Section: Literature Reviewmentioning
confidence: 99%